Pullulan Hydrogels Improve Mesenchymal Stem Cell Delivery into High-Oxidative-Stress Wounds - Wong, Victor W. (2011)
[Image: see text] Cell-based therapies for wound repair are limited by inefficient delivery systems that fail to protect cells from the acute inflammatory environment. Here, a biomimetic hydrogel system is described that is based on the polymer pullulan, a carbohydrate glucan known to exhibit potent antioxidant capabilities. It is shown that pullulan hydrogels are an effective cell delivery system and improve mesenchymal stem cell survival and engraftment in high-oxidative-stress environments. The results suggest that glucan hydrogel systems may prove beneficial for progenitor-cell-based approaches to skin regeneration.